A case of mucus hematometra in a bitch: description and analysis of a treatment with aglepristone and cloprostenol - Sánchez Riquelme, Alfonso (2021)
The case of a 2.5-year-old Dogue de Bordeaux dog brought for consultation due to abundant mucosanguineous vaginal discharge around three weeks after oestrous. At the time of the examination, systemic compromise with fever, dehydration and decay was observed. The gynaecological examination revealed diestrous state (progesterone >10 ng/ml), vaginal cytology with abundant mucus, cellular detritus, and few neutrophils. Ultrasonographically, a distended, saccular uterus with abundant anechoic content was observed. The systemic condition was treated with analgesics and anti-inflammatories (Metamizole, Ketoprofen, Tramadol), and antibiotic therapy (Enrofloxacin) for 7 days. A therapy was established based on Aglepristone, two administrations every 24 h and Cloprostenol, three administrations every 24 h, achieving remission of the condition in one week. The background, evidence and analysis of the case allow postulating the clinical diagnosis of mucohematometra.